Truth, trauma and memory a critical analysis of truth commissions with specific reference to Liberia - Ward, Rachel (Department of Public Law, 2015)
On the 18th August 2003 in the City of Accra, Ghana, representatives of the new Liberian government signed what became known as the Comprehensive Peace Agreement (CPA). The Agreement marked the formal end of over twenty years of civil war and strife for Liberia and the Liberian people. Article XIII of the CPA outlines the establishment of a Truth and Reconciliation Commission (TRC). Accordingly, the Commission was mandated to provide a forum that will address issues of impunity, as well as an opportunity for both the victims and perpetrators of human rights violations to share their experiences in order to get a clear picture of the past to facilitate genuine healing and reconciliation.In essence, the proposal was for individuals to share their experiences, through speech and language, of the violence and inhumane treatment suffered through the years of war, in order to provide the greater community of Liberia with a clearer understanding of their collective history and, as a result, lead the country to realise "genuine healing and reconciliation‟ through this process. Through a philosophical and psychological framework this paper seeks to explore the promises and limitations of truth commissions - with specific refererence to the truth commission established in Liberia - through a deconstruction and discussion of their central elements: truth, testimony, history and reconciliation. The paper will contest the notion posited in the mandates of truth commissions that truth is something objective and verifiable that can be found; rather, I insist that if we align our understanding of truth with Nietzschean thinking on the subject, truth commissions can foster the creation of truth through the individual's creative engagement with speech and language as they testify at truth commission hearings. The paper then goes on to discuss some of the problems inherent in the idea that, through the act of narrative, individuals can heal through a spoken testament of their traumas. Following post-modernist thinking, this paper is sceptical of claims of official truth and history which privileges certain memories and narratives and in fact subscribes to a version of history which suits the agenda of the new order and government, or those who have been tasked with writing this official truth and history. Indeed, by the very notion that truth commissions 'rewrite' the past they admit that truth and history are permeable, biased and privileged to whomever is writing it. This paper argues that despite truth commission's claims that they are therapeutic bodies aimed at the overall healing and betterment of those afflicted by the pains of war, truth commissions are in fact political bodies designed to forward the agenda of the new reigning order. In addition, this paper makes suggestions as to what elements of a truth commission can have a positive and healing effect, and could therefore lead to what I argue to be true and lasting reconciliation. The paper will contest the notion posited in the mandates of truth commissions that truth is something objective and verifiable that can be found; rather, I insist that if we align our understanding of truth with Nietzschean thinking on the subject, truth commissions can foster the creation of truth through the individual's creative engagement with speech and language as they testify at truth commission hearings. The paper then goes on to discuss some of the problems inherent in the idea that, through the act of narrative, individuals can heal through a spoken testament of their traumas. Following post-modernist thinking, this paper is sceptical of claims of official truth and history which privileges certain memories and narratives and in fact subscribes to a version of history which suits the agenda of the new order and government, or those who have been tasked with writing this official truth and history. Indeed, by the very notion that truth commission's 'rewrite' the past they admit that truth and history are permeable, biased and privileged to whomever is writing it. This paper argues that despite truth commission's claims that they are therapeutic bodies aimed at the overall healing and betterment of those afflicted by the pains of war, truth commissions are in fact political bodies designed to forward the agenda of the new reigning order. In addition, this paper makes suggestions as to what elements of a truth commission can have a positive and healing effect, and could therefore lead to what I argue to be true and lasting reconciliation The paper then goes on to discuss some of the problems inherent in the idea that, through the act of narrative, individuals can heal through a spoken testament of their traumas. Following post-modernist thinking, this paper is sceptical of claims of official truth and history which privileges certain memories and narratives and in fact subscribes to a version of history which suits the agenda of the new order and government, or those who have been tasked with writing this official truth and history. Indeed, by the very notion that truth commission's 'rewrite' the past they admit that truth and history are permeable, biased and privileged to whomever is writing it. This paper argues that despite truth commission's claims that they are therapeutic bodies aimed at the overall healing and betterment of those afflicted by the pains of war, truth commissions are in fact political bodies designed to forward the agenda of the new reigning order. In addition, this paper makes suggestions as to what elements of a truth commission can have a positive and healing effect, and could therefore lead to what I argue to be true and lasting reconciliation.